1991
DOI: 10.1128/jb.173.24.7867-7874.1991
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chromosome location of Bacillus subtilis forespore genes on their spo gene dependence and transcription by E sigma F: identification of features of good E sigma F-dependent promoters

Abstract: Translational lacZ fusions to forespore genes of Bacillus subtilis were not expressed in spoIIAC (iF) or spoIIIE mutants when the lacZ fusions were integrated at the loci of the same genes or at the SP,( locus. However, some of these genes, including gerA, gpr, spoIIIG (sG), and sspE, were expressed in spoIIIE mutants and spoIIIE spoIIIG double mutants (but not in spoJIAC mutants) when the lacZ fusions were integrated at the amyE locus. When tested, the I8-galactosidase made in these mutants was found only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 27 publications
7
106
0
Order By: Relevance
“…The csfX open reading frame is preceded immediately by a sequence similar to that found in other (rF-dependent promoters (Sun et al 1991). A DNA fragment containing the csfX gene and only 82 bp of sequence upstream of its putative transcription start was able to fully complement in trans the sporulation defect of the csfX mutant, indicating that all the signals required for correct expression of csfX are located in that short interval.…”
Section: Csfx Is Controlled Exclusively By O Fmentioning
confidence: 90%
“…The csfX open reading frame is preceded immediately by a sequence similar to that found in other (rF-dependent promoters (Sun et al 1991). A DNA fragment containing the csfX gene and only 82 bp of sequence upstream of its putative transcription start was able to fully complement in trans the sporulation defect of the csfX mutant, indicating that all the signals required for correct expression of csfX are located in that short interval.…”
Section: Csfx Is Controlled Exclusively By O Fmentioning
confidence: 90%
“…The B. subtilis strains used in this work are all derivatives of strain 168 and were PS832, a prototrophic derivative of strain 168; PS3207, cwlD Cm r (7); CW355 (obtained from R. Losick, Harvard University, Cambridge, MA), encoding GFP fused to the first 21 codons of the sspE gene under control of the strong forespore-specific sspE-2G promoter with an adjacent K m r (10 g͞ml) marker (29,30); PS3518, sspE-gfp K m r , made by transformation of chromosomal DNA from strain CW355 into PS832 and selection for K m r ; and PS3519, cwlD sspE-gfp Cm r K m r , made by transformation of chromosomal DNA from strain CW355 into PS3207 and selection for K m r . Spores of all strains were prepared at 37°C on 2ϫ SG medium agar plates and harvested, cleaned, and stored as described (31).…”
Section: Methodsmentioning
confidence: 99%
“…Mystifyingly, the Stragier lab had obtained contradictory results with a reporter gene located at the amyE locus, indicating no such role for SpoIIIE (Karmazyn-Campelli et al, 1989). The Setlow lab then showed that the difference between our respective results was due to the chromosomal location of the lacZ reporter gene used to measure s F activation (Sun et al, 1991). Ling Juan Wu's first fluorescence images of the chromosomes of a spoIIIE mutant immediately provided the answer (although it was some time before we recognized this) (Wu & Errington, 1994).…”
Section: Asymmetry and The Determination Of Cell Fatementioning
confidence: 98%